Towards a Targeted Smart Indonesia Card (KIP): Policy Strategies for Improving Scholarship Governance in Madrasas and Islamic Boarding Schools - Munfa'ati (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This policy paper identifies and analyzes the governance issues of the Smart Indonesia Card (KIP) scholarship program at the Ministry of Religious Affairs. The primary issue is the lack of program optimization due to data inaccuracy, complex procedures, and weak coordination. These problems are rooted in a lack of data integration, unclear regulations, and weak socialization, resulting in misdirected scholarships and hampering the program's primary objectives. This paper uses a qualitative method with an ex-post policy analysis approach that examines existing policies. The conceptual framework is developed through a cause-and-effect analysis using the USG (Urgency, Seriousness, Growth) theory to prioritize problems, followed by identifying root causes. Five policy alternatives are then evaluated using the William N. Dunn scoring matrix to determine the most effective solution. The analysis results indicate that implementing a data-driven performance incentive and disincentive policy is the best alternative. Therefore, the proposed policy recommendation is the establishment of a Ministerial Regulation governing the mechanism for providing incentives and disincentives to encourage improvements in data quality and bureaucratic efficiency at all levels, from the central government to educational units. Implementation of this policy is expected to make KIP within the Ministry of Religious Affairs more targeted, equitable, and accountable.